2022
DOI: 10.1111/cas.15267
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of count of extratumoral lymphatic permeation in lung adenocarcinoma and its relation to the immune microenvironment

Abstract: Extratumoral lymphatic permeation (ly-ext) has been reported as an independent poor prognostic factor for lung adenocarcinoma, but whether or not the number of ly-ext foci is associated with prognosis and its relationship to the immune microenvironment is unclear. We counted the number of ly-ext foci on pathological slides from patients with completely resected lung adenocarcinoma with ly-ext, and divided them into two groups: a group with a high number of ly-ext foci (ly-ext high) and one with a low number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The study demonstrated the prognostic value of FOXP3+ and CD8+ for stage IA LUAD. The number of FOXP3+ cells in TILs within the primary lesion was associated with number of extratumoral lymphatic permeation (ly-ext) foci that has been reported as an independent poor prognostic factor for LUAD [62]. The group of Niimi et al observed a significantly higher number of FOXP+ T cells in LUAD patients with an abundance of ly-ext foci [62].…”
Section: Prognostic Significance Of Tumor-infiltrating Foxp3+ T Lymph...mentioning
confidence: 96%
See 2 more Smart Citations
“…The study demonstrated the prognostic value of FOXP3+ and CD8+ for stage IA LUAD. The number of FOXP3+ cells in TILs within the primary lesion was associated with number of extratumoral lymphatic permeation (ly-ext) foci that has been reported as an independent poor prognostic factor for LUAD [62]. The group of Niimi et al observed a significantly higher number of FOXP+ T cells in LUAD patients with an abundance of ly-ext foci [62].…”
Section: Prognostic Significance Of Tumor-infiltrating Foxp3+ T Lymph...mentioning
confidence: 96%
“…The number of FOXP3+ cells in TILs within the primary lesion was associated with number of extratumoral lymphatic permeation (ly-ext) foci that has been reported as an independent poor prognostic factor for LUAD [62]. The group of Niimi et al observed a significantly higher number of FOXP+ T cells in LUAD patients with an abundance of ly-ext foci [62]. Hence, an immunosuppressive environment in LUAD might be additionally defined by extratumoral ly-ext foci.…”
Section: Prognostic Significance Of Tumor-infiltrating Foxp3+ T Lymph...mentioning
confidence: 98%
See 1 more Smart Citation
“…PDT has a poor prognosis and is predisposed to relapse and metastasis, probably attributed to the peritumoral stroma, inflammation level, lymphatic infiltration, vascular infiltration, etc. (16)(17)(18). Nevertheless, the spatial heterogeneity above is tough to be observed in CT images.…”
Section: Introductionmentioning
confidence: 99%